Canadian Association of Gastroenterology Clinical Practice Guidelines: The Use of Infliximab in Crohn's Disease - Remo Panaccione; Richard N Fedorak; Guy Anmais; Charles N Bernstein; Alain Bitton; Ken Croitoru; Robert Enns; Brian Feagan; Marty Fishman; Gordon Greenberg; Anne Griffiths; John K Marshall; et al. (Canadian Journal of Gastroenterology)
These guidelines are presented as a follow-up to the original Canadian Association of Gastroenterology Clinical Practice Guidelines: The use of infliximab in Crohn's disease, published in the Canadian Journal of Gastroenterology (1). The original guidelines represented publications between 1998 and 2000. The current guidelines have been updated to reflect knowledge gained from two pivotal randomized clinical trails, with the use of infliximab in the maintenance of inflammatory Crohn's disease in remission (2) and in the maintenance of fistulous Crohn's disease in remission (3).